Technical Territories: Data, Subjects, and Spaces in Infrastructural Asia - Munn, Luke (University of Michigan Press, 2023)
Territory is shifting. No longer defined by the dotted line of the border or the national footprint of soil, today’s territories are enacted through data infrastructures. From subsea cables to server halls, these infrastructures underpin new forms of governance, shaping subjects and their everyday lives. Technical Territories moves from masked protestors in Hong Kong to asylum-seekers in Christmas Island and sand miners in Singapore, exploring how these territories are both political and visceral, altering the experience of their inhabitants. Infrastructures have now become geopolitical, strategic investments that advance national visions, extend influence, and trigger trade wars. Yet at the same time, these technologies also challenge sovereignty as a bounded container, enacting a more distributed and decoupled form of governance. Such “technical territories” construct new zones where subjects are assembled, rights are undermined, labor is coordinated, and capital is extracted. The stable line of the border is replaced by more fluid configurations of power. Luke Munn stages an interdisciplinary intervention over six chapters, drawing upon a wide range of literature from technical documents and activist accounts, and bringing insights from media studies, migration studies, political theory, and cultural and social studies to bear on these new sociotechnical conditions.